2018
DOI: 10.1107/s2053230x18006118
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II microcrystals suitable for XFEL studies

Abstract: Recent advances in X-ray free-electron laser (XFEL) sources have permitted the study of protein dynamics. Femtosecond X-ray pulses have allowed the visualization of intermediate states in enzyme catalysis. In this study, the growth of carbonic anhydrase II microcrystals (40-80 µm in length) suitable for the collection of XFEL diffraction data at the Pohang Accelerator Laboratory is demonstrated. The crystals diffracted to 1.7 Å resolution and were indexed in space group P2, with unit-cell parameters a = 42.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…Hence, they may be detected only in time resolved experiments employing, for instance, serial femtosecond crystallography . Although the synthesis of HCA II microcrystals, needed for such studies, has been recently reported, no further time‐resolved data are available in the literature as yet. The only relevant experimental study based on time‐resolved X‐ray absorption spectroscopy detected fast variations between tetra‐ and penta‐coordinated states at the catalytic zinc site of bacterial alcohol dehydrogenase .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they may be detected only in time resolved experiments employing, for instance, serial femtosecond crystallography . Although the synthesis of HCA II microcrystals, needed for such studies, has been recently reported, no further time‐resolved data are available in the literature as yet. The only relevant experimental study based on time‐resolved X‐ray absorption spectroscopy detected fast variations between tetra‐ and penta‐coordinated states at the catalytic zinc site of bacterial alcohol dehydrogenase .…”
Section: Introductionmentioning
confidence: 99%
“…With one of the fastest known biological reactions, CA is an ideal candidate for such SFX experiments to map the movements of substrate/product through the active site. Microcrystals of CA II suitable for XFEL data collection have recently been produced and confirmed to diffract at the Pohang Accelerator Laboratory XFEL [ 153 ]. A further benefit is the collection of diffraction data at room temperature before the onset of radiation damage.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 . Further, special sample containers can be coupled to the setup, which can be also utilized for real-time investigations to follow the crystallization process of biomolecules 34,35 . Fortunately, there are very little limitations for different types of sample containers, which can be applied, owing to a flexible platform of the MPM system.…”
Section: Methodsmentioning
confidence: 99%
“…It offers new opportunities in structural biology, e.g., allowing data collection at room temperature and to perform time-resolved experiments 5 7 . The size and dimensions of protein crystals required for diffractive imaging at high-brilliance micro-focus X-ray sources is continuously decreasing, down to a few micrometers or even sub-micrometer regime 8 , 9 . In this context, the demand to produce, detect, and, in particular, to monitor and image crystal suspensions upon preparation and just prior to data collection has substantially increased 10 .…”
Section: Introductionmentioning
confidence: 99%